The Impact of COVID-19 Pandemic on Economics, Accounting Practice, Research and Quality of Education in the Slovak Republic: Lessons Learnt - Mokošová, Daša; Blahušiaková, Miriama; Dyczkowska, Joanna (Publishing House of Wroclaw University of Economics and Business, 2023)
[The monograph provides an in-depth analysis of the pandemic impacts on the macroeconomic environment and the economic situation of entities at the micro level. It presents the fiscal and financial measures taken by the EU, and in particular by the Slovak Republic, as a Member State of the EU. The monograph also assesses the pandemic's impacts on accounting practice, education, science, and research in the Slovak Republic and presents solutions applied in these areas. This book is addressed to academia, the scientific community, as well as to all those who want to learn from the pandemic consequences using the Slovak Republic as an example.] nota z zapowiedzi wydawniczej
s. 161
Keywords: COVID-19; fiscal and financial measures; pandemic impact; European Union; Slovak Republic